No Shipping Fees or Free Shipping? Impact of Temporal Proximity on the Relative Effectiveness of Promotional Framing - Kulkarni, Atul A. (Journal of Promotion Management, 2020)
In this research, we find that the relative effectiveness of framing a shipping promotion as “no shipping fees” versus “free shipping” may depend on temporal proximity of the promotional offer. Our findings suggest that when the promotion is on offer in immediate future, framing it as no shipping fees is relatively more effective. In contrast, when the promotion is on offer in relatively distant future, framing is as free shipping is relatively more effective. Our findings also suggest that these differences in the relative effectiveness of the two framing types may be subject to the degree of elaboration. The differences may manifest when consumers process promotional information cursorily but may dissipate when consumers elaborate more. When primed to process information cursorily, participants in our studies (Studies 1 and 2) reported higher offer evaluations and purchase intentions when (i) an ongoing promotion was framed as no shipping fees or (ii) a promotion available in the future was framed as free shipping. These effects dissipated when either the participants were primed to elaborate more (Study 3) or when the temporal aspect was eliminated (Study 4).
_eprint: https://doi.org/10.1080/10496491.2019.1612493
Keywords: dept.mrk; evaluation; framing; free shipping; peer-reviewed; promotions; temporal distance

Conspicuous gifting: When and why women (do not) appreciate men's romantic luxury gifts - Ding, William; Pandelaere, Mario; Slabbinck, Hendrik; Sprott, David E. (Journal of Experimental Social Psychology, 2020)
While research suggests that conspicuously displaying luxury goods can help men signal desirable qualities such as high earning capacity and social status, little is known about how women evaluate and interpret luxury items given as romantic gifts by men. The current research explores this under-researched question and reveals that women do not always react favorably to luxury gifts. Instead, women are wary that accepting luxury gifts may lead to relationship power imbalance, which prompts less favorable reactions to such gifts. We also test the competing explanation of relationship commitment and find that signaling commitment does not emerge until a relationship becomes more established. Furthermore, individual differences in power distance belief (PDB) are explored to test our theoretical explanation with results indicating that women low in PDB are more likely to have concerns about power imbalance. Together, these findings highlight the unique role of luxury gifts in romantic relationships and thereby advance our understanding of when and why men's romantic luxury gifts will be appreciated by women. More generally, our findings provide nuanced insights into the power dynamics between men and women and the progression of a romantic relationship. Implications for luxury consumption and gender stereotypes are discussed.
Keywords: Conspicuous consumption; Gift giving; Power imbalance; Relationship norm; dept.mrk; peer-reviewed

The effect of mindfulness on service encounter quality - Wang, Emma Junhong; Berthon, Pierre R.; Bechwati, Nada Nasr (Journal of Services Marketing, 2020)
Purpose This paper aims to explore the effect of employees’ state mindfulness, a short period of mindful presence, on the quality of the service they provide in a service encounter. Design/methodology/approach Three studies are conducted. A pilot study explores the relationship between state mindfulness and service encounter quality. Experiment 1 examines whether a 15-min mindfulness exercise results in an increase in service employees’ state mindfulness. Experiment 2 tests whether induced state mindfulness produces higher service quality and whether a reminding technique can prolong state mindfulness between service encounters. Findings The results demonstrate the following. First, that more mindful employees provide better service quality. Second, that a short, easily implemented, mindfulness exercise can reliably increase employees’ state mindfulness. Third, induced mindfulness has an impact on subsequent service quality in terms of reliability, assurance, empathy and responsiveness. These effects persist regardless of the service encounter structure (high vs low structure) or the degree of emotional labor involved (high vs low emotionally charged). Finally, the reminding technique developed as part of this research suggests that state mindfulness can be maintained between service encounters. Research limitations/implications As simulated (programmed) customers are used, independent evaluators to assess service quality are used. Service providers in this study are college students; future field studies should consider a wider range of service providers. The research focuses on state mindfulness; exploration of trait mindfulness offers future research opportunities. Originality/value To the best of the authors’ knowledge, this research is the first to empirically examine the link between mindfulness and service quality. It shows that mindfulness can be induced, and through a reminding technique be maintained, and improve service quality across service interactions. This is a powerful finding for marketing managers, for it offers a new method to enhance service provision. Moreover, this research implies that the increase in service quality is likely to be accompanied by reduced job burnout: a double win for employees, employers and customers.
7 citations (Crossref) [2023-10-31]
Keywords: Emotional labor; Induced state mindfulness; Mindfulness; Service encounter quality; Service encounter structure; dept.mkt; peer-reviewed

Exploring the optimized social advertising strategy that can generate consumer engagement with green messages on social media - Kyu Kim, Young; Yim, Mark Yi-Cheon; Kim, Eunjin; Reeves, William (Journal of Research in Interactive Marketing, 2020)
Purpose: Given that many consumers are skeptical about environmentally based advertising campaigns, the purpose of this study is to propose an optimized message strategy to facilitate consumer engagement with green messages in social media contexts. Design/methodology/approach: Four empirical studies are conducted using self-report questionnaires to test proposed hypotheses with a focus on the interplay between claim specificity and benefit appeals in green advertising on social media. Findings: The current study examines the interaction effects of claim specificity and benefit appeals on consumer engagement in social media. Specifically, the results reveal that when the message claim is abstract, using other-benefit appeals produces more positive consumer engagement than using self-benefit appeals. Moreover, the results illustrate that self-enhancement motivates consumers to engage with green product advertising messages when the advertising appeal is abstract and the advertising message is associated with benefits for others. Finally, it is found that consumers’ self-construal level moderates the interaction effect of claim specificity and benefit appeals type on consumer engagement on social media. Practical implications: This paper has practical implications to both social media managers and advertisers in the green product industry: a match with advertising claim specificity and construal level (i.e. social distance: self-benefit vs other-benefit) should be ensured to increase consumer engagement on social media. In addition, self-enhancement and self-construal should be considered for a better message strategy in social media contexts. Originality/value: The findings make important contributions to the literature in that we extend the applications of construal level theory to social media contexts as a valid theoretical tool to identify optimized green message strategies. As such, it provides future researchers and practitioners in the domain of green campaigns with useful guidelines to boost more consumption of green products. © 2020, Emerald Publishing Limited.
29 citations (Crossref) [2023-10-31] WOS:000607792100001
Keywords: Online consumer behavior; Social media advertising; dept.mkt; peer-reviewed

Cultural adaptation and consumer disidentification in the us - Prince, M.; Kwak, L (Journal of Empirical Generalisations in Marketing Science, 2020)
Alexander Josiassen (2011) initiated research on the consumer disidentification (CDI). More specifically, in his investigation of 2nd generation Turks in the Netherlands, he introduced the concept of acculturation as an antecedent to consumer disidentification among this ethnic group. Josiassen's study showed that acculturation negatively affects CDI. The present replication research among American 2nd generation US immigrants confirmed Josiassen’s findings with respect to CDI. It also confirmed his findings that acculturation positively affects consumer ethnocentrism (CET). In elaborating his model, the US study found that (a) national disidentification (NDI) is inversely predictive of acculturation, and (b) acculturation is negatively predictive of consumer xenocentrism (XEN). Replication of the Netherland CDI model in the U.S. results in an acceptable measurement fit and structural fit. © 2020, University of South Australia. All rights reserved.
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85096865217
Keywords: Consumer disidentification; Cross-cultural; Ethnocentrism; National disidentification; Xenocentrism; dept.mkt; peer-reviewed; ⛔ No DOI found

Genetically modified crops’ environmental impact and trust in eco-labels - Kwak, Lynn E.; Yoon, Sang Won; Kim, Younjun (Australasian Marketing Journal, 2020)
The U.S. Department of Agriculture expects companies to disclose genetically modified (GM) ingredients in foods and beverages by January 2022. While food companies fear that the stigma of GM labels could cause GM food sales to decline, eco-labeling could lessen the impact of GM-labeling. The results of the present research indicate that neither the eco-labeling alone nor the eco-labeling accompanied by information about the environmental benefits of GM crops influence consumers’ willingness to buy. Based on the mediation analysis, however, trust of eco-labels mediates the relationship between GM foods’ environmental friendliness information and consumers’ willingness to buy eco-labeled GM food. The theoretical and practical implications of the findings are discussed. © 2020
4 citations (Crossref) [2023-10-31] tex.ids: kwakGeneticallyModifiedCrops2020a
Keywords: Eco-labeling; Genetically modified (GM) foods; Trust; Willingness to buy; dept.eco; dept.mkt; peer-reviewed

Domestic Product Involvement and Consumer Willingness to Buy Domestic Products: Empirical Testing of a Cognitive Consistency Theory Framework - Prince, Melvin (Journal of International Consumer Marketing, 2020)
This study investigates biases affecting domestic products willingness to buy (WTB). An interdisciplinary perspective uses the cognitive consistency theory as the framework for the development of a new model. The model includes domestic product involvement (DPI). The impact on WTB is predicted by consumer ethnocentrism, and product judgment, driven by DPI are tested with survey data from an adult sample of 255 UK consumers. The study concludes with observations about the value of research findings for marketing practice. © 2020 Taylor & Francis Group, LLC.
7 citations (Crossref) [2023-10-31] WOS:000517943000001
Keywords: Cognitive consistency theory; consumer ethnocentrism; dept.mkt; domestic product involvement; peer-reviewed; product judgment; willingness to buy

Does the Netherlands-based consumer disidentification model work in the US? - Prince, Melvin; Kwak, Lynn (EMPGENS | Journal of Empirical Generalisations in Marketing Science, 2020)
Alexander Josiassen (2011) initiated research on the consumer disidentification (CDI) concept and its impact on product purchase behavior. In his investigation, a predictive model that included CDI as an exogeneous factor in domestic product preference was tested on adult second-generation immigrants who were born in, and lived in, the Netherlands. The model also incorporated consumer ethnocentrism (CET) as a second predictor variable. Josiassen's study showed that CDI negatively affected the purchase of products made domestically or by domestic firms. Conversely, CET was found to have a positive effect on the purchase of these products. Furthermore, relationships of CDI and CET to purchase intentions were independent of each other. In the Netherlands model, both variables were hypothesized to explain domestic product preference directly and indirectly through domestic product judgment. This paper replicates and assesses the generalizability of the CDI construct and model. Replication of the Netherland CDI model in the U.S. results in an acceptable measurement fit, but a slightly below acceptable structural fit. © 2020, University of South Australia. All rights reserved.
tex.ids: princeDoesNetherlandsbasedConsumer2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85091584869 type: Article
Keywords: Consumer disidentification; Cross-cultural; Domestic product preference; Ethnocentrism; Second-generation immigrants; dept.mkt; peer-reviewed; ⛔ No DOI found

The psychology of consumer ethnocentrism and cosmopolitanism: a five-country study of values, moral foundations, gender identities and consumer orientations - Prince, Melvin; Yaprak, Attila; Cleveland, Mark; Davies, Mark A. P.; Josiassen, Alexander; Nechtelberger, Andrea; Nechtelberger, Martin; Palihawadana, Dayananda; Renner, Walter; Supekova, Sona Chovanova; Von Wallpach, Sylvia (International Marketing Review, 2020)
Purpose: The purpose of this paper is to examine the extent to which personal values, moral foundations and gender-role identities affect, in sequence, consumers' constructions of their ethnocentric and cosmopolitan orientations. Achieving a better understanding of the psychological makeup of consumer ethnocentrism and cosmopolitanism should help managers better design international market segmentation and brand positioning strategies. Design/methodology/approach: The study's conceptual framework is anchored in attitude and values theories, and focuses on the social categorizations that consumers make and how these contribute to the formation of their ethnocentric and cosmopolitan orientations. Drawing data from consumers living in five European countries, we test our theoretical conjectures through structural equation modeling approaches, including multigroup analysis at the country level, as well as the identification and scrutiny of potential pan-European consumer segments. Findings: Findings show that personal values, moral foundations and gender-role identities do exert direct and indirect (partially mediated) effects on the formation of consumers' ethnocentric and cosmopolitan orientations. These provide numerous insights for managers in terms of how they can segment domestic and international markets, as well as how to position products and communicate brand strategies. Research limitations/implications: The study focused on consumers' personal and role identities and offers implications based on data gathered from a sample of five European countries. Future work should broaden this perspective by including other identity facets, such as religious and ethnic identities, as well as product-category and brand-specific outcomes, in order to help develop a more comprehensive picture of the psychology underpinning consumers' identity-related orientations, and their effects on consumer behavior. Future research should also study these issues in a broader geographical context, by including national markets that have culturally diverse populations as well as places with dissimilar cultural and economic profiles. Originality/value: The study shows that individuals' personal values, moral foundations and gender roles have a strong effect on the formation of consumer ethnocentrism and consumer cosmopolitanism orientations. Consideration of how these antecedent constructs operate in concert to shape consumers' in- versus out-group orientations has been overlooked in the international marketing literature. Beyond the ramifications for theory, the study offers numerous substantive managerial implications in terms of how consumers are likely to respond to local and global/foreign products/brands based on these orientations. © 2020, Emerald Publishing Limited.
18 citations (Crossref) [2023-10-31] WOS:000537142600001
Keywords: Consumer cosmopolitanism; Consumer ethnocentrism; Gender role identity; International market segmentation; Moral foundations; Values; dept.mkt; peer-reviewed

How to easily facilitate consumers’ mental simulation through advertising: the effectiveness of self-referencing image dynamics on purchase intention - Yim, Mark Yi-Cheon; Kim, Young K.; Lee, JeongGyu (International Journal of Advertising, 2020)
10 citations (Crossref) [2023-10-31] tex.ids: yimHowEasilyFacilitate2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088955581 type: Article
Keywords: dept.mkt; peer-reviewed

Mindful consumption: Three consumer segment views - Milne, George R.; Ordenes, Francisco Villarroel; Kaplan, Begum (Australasian Marketing Journal, 2020)
As consumers are moving away from mindless consumerism, a mindful consumption literature has emerged that is based on Buddhist and psychological perspectives of mindfulness. While the idea of mindful consumption has great potential, there is little empirical research to date that comprehensively examines the consumer perspective on the role of mindfulness on consumption. To provide a grounded consumer perspective, the authors segment mindful consumption views from open-end text using a mixed method of clustering and text mining. By analyzing the segmentation structure, the authors discover various consumer views of mindful consumption, such as careful economic based consumption, monitoring activities of firms, and being informed about the impact of consumption choices. The authors compare the empirical results with the academic literature to provide directions for future research. © 2019 Australian and New Zealand Marketing Academy
40 citations (Crossref) [2023-10-31] tex.ids: lens.org/017-626-502-015-133, milneMindfulConsumptionThree2020a, pop00147 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85072713622 tex.type: [object Object] type: Article
Keywords: Mindful consumption; Mindfulness; Segmentation; Sustainability; Text mining; dept.mkt; peer-reviewed